PERAN LABA KOTOR, AKTIVITAS OPERASIONAL, AKTIVITAS INVESTASI, DAN AKTIVITAS PENDANAAN ARUS KAS TERHADAP RETURN SAHAM - Wardana, Ditya; Fauziah, Satya (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2024)
This research aims to analyze the effects of gross profit, and cashflow activity on stock returns by taking the population of this study, namely consumer goods companies listed on the Indonesia Stock Exchange in 2018-2019. In order to find 30 organizations that fit the criteria for the research sample, a purposive sampling method was utilized in the sampling process. SPSS is used for data analysis, including multiple regression and hypothesis testing. Based on the results of analysis and hypothesis testing, it was found that (1) gross profit did not affect stock returns, so the first hypothesis was rejected; (2) stock returns are unaffected by cash flow from operating activities, so the second hypothesis is rejected; (3) Investing activity cash flows have an impact on stock returns, so the third hypothesis is accepted; (4) sock returns are unaffected by cash flows from financing activities, so the fourth hypothesis is rejected. An rise in investment cash flow will entice more investors to participate, which will raise demand for the company and drive up stock prices.